Evaluation of the Impact of the Thrifting Ban Policy at Gedebage Market Bandung City - Albari, Diva Septiansyah; Rahardian, Ramaditya; Yusup, Rikki Maulana; Andri, Yayan; Sofyan, Meti Mediyastuti (Journal of Social and Policy Issues, 2025)
The issue of used clothing, or trifling, has become a significant concern for the government and the wider public today, both in social and print media. This study analyzes the impact of the policy banning the sale of used clothing at Gedebage Market, Bandung, which was implemented to protect the local textile industry and reduce textile waste. Using a descriptive qualitative approach with data collection techniques such as interviews and documentation studies, the findings of this study found that the policy banning the trifling trade had a significant impact on various aspects of life. Economically, traders experienced a decrease in income and some were forced to close their businesses. Socially, people lost access to affordable clothing and resistance emerged. From a political perspective, there was debate about the fairness of the policy and the lack of public involvement in its formulation, which directly impacted traders. Meanwhile, from an environmental perspective, this policy is considered to have positive potential in reducing textile waste, although it still requires further policy support such as the provision of facilities. This study recommends various participatory and inclusive policy evaluations in the implementation of policies related to the ban on trifling in the Cimol Gedebage market in Bandung City, by considering several aspects of balance, including the economic interests of the community and environmental sustainability that encourage efforts not to marginalize traders who sell used clothes in the Cimol Gedebage market in Bandung City.